Efficacy and safety of convalescent plasma therapy in patients with COVID-19: arapid review of case series - David Dwi Putera; Mardiah Suci Hardianti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) has become a world pandemic since early 2020.Currently, there is no established treatment to combat this potentially fatal disease. Convalescent plasma (CP) therapy has a strong scientific basis and historical perspective to treat previous viral infections such as Ebola, Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS). The aim of this review was to evaluate the efficacy and safety of convalescent plasma CP therapy in patients with COVID-19.We searched for every available study from major databases (CENTRAL, MEDLINE via Ovid, EMBASE) through 20th April 2020. We independently screened, extracted, assessed the risk of bias, analyzed the data using SPSS version 26, and narratively summarized the data. For the outcomes, we wanted to evaluate the changes of clinical parameters, radiological appearance, pulmonary function, the titer of neutralizing antibody, viral load, the disappearance of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) RNA, and adverse events.We found five case series from our literature searching. The overall methodological quality of the case series was moderate. We included 27 patients, and all patients received CP transfusion. All patients experienced improvement of clinical symptoms and pulmonary lesions after receiving 200 to 2400 mL (median 200 mL) of CP transfusion. All patients in reported studies had negative results of reverse transcriptase-polymerase chain reaction(RT-PCR) after 1 to 26 days of transfusion (median 3 days). There was one non-life threatening adverse event reported after CP transfusion (facial red spot). In conclusion, CP therapy in COVID-19 patients showed promising results as it improved clinical symptoms and parameters, and it is well-tolerated based on our included studies. However, further expanded clinical trials with better designs are still required to evaluate the efficacy of this treatment although suchidea will be quite challenging to be conducted in the era of an epidemic.